Pelopscreadium aegyptense n. gen., n. sp. and Pelopscreadium spongiosum (Bray & Cribb, 1998) n. comb., (Digenea: Lepocreadiidae), each from disjunct populations of the Yellow boxfish, Ostracion cubicus Linnaeus (Ostraciidae) - Dronen, Norman O.; Blend, Charles K.; Khalifa, Refaat M. A.; Mohamadain, Hoda S.; Karar, Yasser F. M. (Zootaxa, 2016)
Bianium spongiosum Bray & Cribb, 1998 (Lepocreadiidae), described from the yellow boxfish, Ostracion cubicus Linnaeus (Ostraciidae), off Lizard Island, Queensland, Australia, possesses a combination of the following three morphological features which distinguishes it from all the other species currently assigned to the genus: (1) large internal patches of large cells forming sponge-like pads we have termed “pelops”(“pelop” sing.) laterally in the forebody extending from near the anterior extremity to about the level of the intestinal bifurcation rather than possessing a scoop; (2) ceca that reach to near the posterior extremity where they end blindly without ani; and (3) a vitellarium which is present laterally but not dorsal to the ceca. Based on this we propose the erection of Pelopscreadium n. gen. (Lepocreadiidae) with the assignment of B. spongiosum to this new genus as the type-species, Pelopscreadium spongiosum (Bray & Cribb, 1998) n. comb. Pelopscreadium aegyptense n. sp., also from the yellow boxfish but from the Red Sea off Sharm El-Naga, Egypt, is described as the second member of the new genus because it shares these three characteristics with P. spongiosum.